Writing the Lagosian Homeland: the ambiguous and precarious African urban in Chris Abani's GraceLand (2004) - Ohajunwa, Dionne (Department of English Language and Literature, 2025)
Located at the intersection of Urban Geographies and Literary Studies, this study focuses on urban geographical considerations as they are applied to the depiction of the city of Lagos, Nigeria in Chris Abani's novel GraceLand published in 2004. While exploring the cartographies of urban space in the novel, the study applies principles and theories of Southern Urbanisms, notably AbdouMaliq Simone, Ato Quayson, Edgar Pieterse and so much more to reading Lagos as a representation of the African urban. The study offers a critical exploration of the ways that the city of Lagos is mapped by the diasporic author - firstly, on the Noir genre and any possible connections to be made to the novel; secondly on the perception of the homeland and how this feeds into the mapping of the city in the text; thirdly on the lived experiences of those who reside in the city, particularly the perspective of the main character who presents as a type of flaneur within it. The study ultimately hopes to highlight inherent complexities and ambiguities and contribute towards a modification of global perceptions of the African urban